Speech-In-Character, Diatribe, and Romans 3 : Who's Speaking When and Why It Matters. - King, Justin. (Biblical Interpretation Series, 2018)
In Speech-in-Character, Diatribe, and Romans 3:1-9 , Justin King argues that the rhetorical skill of speech-in-character ( prosopopoiia, sermocinatio, conformatio ) offers a methodologically sound foundation for understanding the script of Paul's imaginary dialogue with an interlocutor in Romans 3:1-9. King focuses on speech-in-character's stable criterion that attributed speech should be appropriate to the characterization of the speaker. Here, speech-in-character helps to inform which voice in the dialogue speaks which lines, and the general goals of diatribe help shape how an "appropriate" understanding of the script is best interpreted. King's analyses of speech-in-character, diatribe, and Romans, therefore, make independent contributions while simultaneously working together to advance scholarship on a much debated passage in one of history's most important texts.